Key elements that drive innovative teaching & learning in higher education - Fauzan, Javaria; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Teaching and learning are two essential components of any academic/education system which are also two qualitative factors, too. The advancement of ICT (Information and Communication Technology) has changed the way we experienced the facilities of integrating IT (Information and Technology) and Communication in almost every facet of our life, from business to education and entertainment. Academic policy planners and other key personnel of the education sector are always putting much of their efforts to make the teaching process more effective so that the students can get exactly what the teachers are destined to deliver. This paper will briefly discuss about the key driving elements that could bring significant impact on innovative teaching and learning, particularly in higher education.